Plasmodium falciparum dihydrofolate synthase (DHFS-FPGS) : gene synthesis and recombinant expression - Louw, Abraham Izak (University of Pretoria, 2013)
Dissertation (MSc(Biochemistry))--University of Pretoria, 2006.